1992
DOI: 10.1002/eji.1830221017
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine kinase activation in thymic epithelial cells: necessity of thymocyte contact through the gp23/45/90 adhesion complex

Abstract: Interactions between thymocytes and thymic stromal cells are necessary for T cell differentiation, maturation and proliferation. The signals required for these events to occur often necessitate close contact, and indeed adhesion, between the cell types involved. While the transmission of signals from stromal cells to thymocytes has been well documented, there is little evidence that binding of thymocytes to stromal cells can result in stromal cell activation. We have recently identified a novel thymic epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1993
1993
1997
1997

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…A second type of medullary epithelial cell expresses high levels of MHC class 11 or class I, B7 molecules [5, Development of cortical and medullary cell types requires the presence of thymocytes which were shown to provide organizing [ 131 or growth-promoting signals [ 151. In vitro, activation [32] or growth [33] of medullary stromal cell lines can be modulated by thymocytes. Our results show that the development of two medullary epithelial cell subsets is not synchronous.…”
Section: Discussionmentioning
confidence: 99%
“…A second type of medullary epithelial cell expresses high levels of MHC class 11 or class I, B7 molecules [5, Development of cortical and medullary cell types requires the presence of thymocytes which were shown to provide organizing [ 131 or growth-promoting signals [ 151. In vitro, activation [32] or growth [33] of medullary stromal cell lines can be modulated by thymocytes. Our results show that the development of two medullary epithelial cell subsets is not synchronous.…”
Section: Discussionmentioning
confidence: 99%
“…Although the func tion o f the medullary epithelium is unclear, clonal deletion is manifest in this region (even if induced in the cortex) and the epithelium can induce tolerance in the form o f anergy [24][25][26]. Medullary epithelium also forms stromal cell complexes with thymocytes which may be maturation link ed [27,28] and possibly related to emigration [29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Of importance here is that influences may come from mesenchymal ''passenger'' leukocytes that influence the organization of the thymic stationary microenvironment (Palmer et al, 1993). In vitro studies have shown that lymphocytes induce protein phosphorylation (Couture et al, 1992) and marker expression in cultured epithelial cells (Small et al, 1989). Interestingly, this epithelial differentiation can be induced not only by T cells bearing the ab-T-cell receptor (representing the major population of lymphocytes in the normal thymus), but also by T cells bearing the gd-T-cell receptor: in mice transgenic for a Vg-T-cell receptor, Ferrick et al (1990) even have observed a medullary hyperplasia.…”
Section: Introductionmentioning
confidence: 99%